Eksistensi Korean Street Food Ramah Muslim Dalam Meningkatkan Kesejahteraan UMKM di Kecamatan Kedungwuni Kabupaten Pekalongan - Karimah Frieda (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The Korean Wave has had a significant impact on South Korea's global image, and its products now dominate various industries, including beauty, entertainment, and food. The purpose of this study was to determine the existence of Muslim-friendly Korean Street Food in improving the welfare of MSMEs in Kedungwuni sub-district, Pekalongan district. Qualitative research methodology is used in this study. Observations, interviews, and documentation were used as data collection approaches. Data reduction (data reduction), data display (data presentation), and conclusion drawing/verification are three technical processes of data analysis. The results of the study show that the Korean Wave has succeeded in achieving its popularity in Pekalongan, precisely in Kedungwuni District, through this social media many business actors take advantage of the existence of the Korean Wave to increase their business by selling Korean Street Food. This can be seen from the number of shops or places to eat with Korean Street Food menus. Korean food sold at Korean Street Food shops in Kedungwuni District include Tteokbokki, Hweori Gamja/Tornado Potatoes, Hottang, Corndog and Korean-style Seafood Meatballs.